Algerian secondary school students' preferences for the use of YouTube in their informal learning - Khabbab Meziane Cherif; Lahcene Azzouz; Ahmed Bendania (Academy of Cognitive and Natural Sciences, 2024)
Various technological tools are adopted in the learning process to help students access available knowledge on the net. Due to the COVID-19 pandemic, many Algerian teachers relied more on social network sites, such as YouTube and other applications, to provide their students with lessons. The current study sought to determine the types of videos that Algerian secondary school learners prefer. The study sample included 413 secondary-level students (66% females and 34% males). A short four-question questionnaire was used to collect data. The results indicated that students spent more than 4 hours online daily. They preferred educational content in short videos of 10 minutes at maximum, as well as videos containing content related to materials and exercises pertinent to baccalaureate exercises and/or a presentation about methods of solving exercises without the presence of a teacher's picture. The study suggested recommendations on the importance of using the available technological tools and training teachers in ICT in education.